Influences of Extrusion and Silver Content on the Degradation of Mg-Ag Alloys In Vitro and In Vivo. (23rd April 2022) - Liu, Guanqi; Han, Jianmin; Yu, Xiaodong; Yuan, Shenpo; Nie, Zhihua; Qiu, Tiancheng; Yan, Ziyu; Tan, Chengwen; Guo, Chuanbin
Abstract : Binary magnesium-silver (Mg-Ag) alloys were designed as antibacterial materials for biomedical implant applications. In the present study, we focused on the effects of extrusion (extrusion ratio (ER): 1, 7.1, and 72.2) and Ag content (Ag = 0, 3, and 6 wt.%) on the degradation of Mg-Ag alloys in vitro and in vivo via microstructure characterization and corrosion/degradation measurements. The results showed that the Ag promoted a galvanic reaction with the Mg matrix to accelerate degradation or formed a protective oxide mesh texture to inhibit degradation, especially in vivo . Ag might also be beneficial for product crystallization, biomineralization, and organic matter deposition. For pure Mg, extrusion produced a more refined grain and decreased the degradation rate. For the Mg-Ag alloys, a low extrusion ratio (7.1) accelerated the degradation caused by the increase in the proportion of the precipitate. This promoted the release of Mg 2+ and Ag +, which led to more deposition of organic matter and calcium phosphate, but also more H2 bubbles, which led to disturbance of product deposition in some local positions or even inflammatory reactions. Extrusion at a higher ratio (72.2) dissolved the precipitates. This resulted in moderate degradation rates and less gas production, which promoted osteogenesis without an obvious inflammation reaction.